Mengembangkan Keterampilan Bahasa Produktif yang Dibutuhkan di Era Modern: Bagaimana Menulis dan Berbicara Dapat Membantu Anda Berkomunikasi Lebih Baik di Kehidupan Sehari-Hari - Eveline Stephani; Nurul Azizah; Jihan Anisah Ritonga; Nurul Dwi Dara Auliya; Romatua Harianja; Tivani Aurel Genora Sihombing (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Productive language skills play a very important role in supporting communication in the modern era which is marked by rapid development in various aspects of life. This ability is the main foundation in conveying information clearly, building harmonious social relationships, and achieving success in the professional world. This article discusses in depth the importance of productive language skills and provides practical guidance for developing them through consistent practice, understanding the audience, and applying appropriate communication techniques. By having these skills, individuals can more easily face complex and dynamic challenges, including situations that require clarity, accuracy, and flexibility in communication. In addition, effective communication skills also help individuals increase their competitiveness, both in social interactions and the work environment. Mastery of these skills is becoming increasingly relevant to achieving success in various aspects of daily life in the midst of the ever-changing modern era.